Meta-analysis of randomized controlled trials only exploring the role of single incision laparoscopic surgery versus conventional multiport laparoscopic surgery for colorectal resections - Hebbar, Madhusoodhana; Riaz, Waleed; Sains, Parv; Baig, Mirza Khurrum; Sajid, Muhammad Shafique (Translational Gastroenterology and Hepatology, 2018)
Background: The objective of this article is to evaluate the surgical outcomes in patients undergoing single incision laparoscopic surgery (SILS) versus conventional multi-incision laparoscopic surgery (MILS) for colorectal resections. Methods: The data retrieved from the published randomized controlled trials (RCTs) reporting the surgical outcomes in patients undergoing SILS versus MILS for colorectal resections was analysed using the principles of meta-analysis. The combined outcome of dichotomous data was represented as risk ratio (RR) and continuous data was shown as standardized mean difference (SMD). Results: Five RCTs on 525 patients reported the colorectal resections by SILS versus MILS technique. In the random effects model analysis using the statistical software Review Manager 5.3, the operation time (SMD, 0.20; 95% CI, −0.11 to 0.52; z=1.28; P=0.20), length of in-patient stay (SMD, −0.18; 95% CI, −0.51 to 0.14; z=1.10; P=0.27) and lymph node harvesting (SMD, 0.09; 95% CI, −0.14 to 0.33; z=0.76; P=0.45) were comparable between both techniques. Furthermore, post-operative complications (RR, 1.00; 95% CI, 0.65–1.54; z=0.02; P=0.99), post-operative mortality, surgical site infection rate (RR, 3.00; 95% CI, 0.13–70.92; z=0.68; P=0.50), anastomotic leak rate (RR, 0.43; 95% CI, 0.11–1.63; z=1.24; P=0.21), conversion rate (P=0.13) and re-operation rate (P=0.43) were also statistically similar following SILS and MILS. Conclusions: SILS failed to demonstrate any superiority over MILS for colorectal resections in all post-operative surgical outcomes.